Bioaccumulation of Heavy Metals in Horseshoe Crabs (Tachypleus gigas) from Pekan, Pahang, Malaysia - Yunus, Kamaruzzaman; John, Akbar; Megat, Aqilah; Kassim, Zaleha (Academic Journals Inc., 2011)
An attempt was made to determine the various heavy metal accumulative concentrations in different body parts of horseshoe crab [Tachypleus gigas (Muller, 1785)]. Heavy metal accumulation levels were determined using Inductively Coupled Plasma Mass Spectrometry (ICP-MS). Highest mean concentration (μg g-1 wet weight) of iron (Fe), Zinc (Zn), Copper (Cu) and Cadmium (Cd) was observed in gill tissue (1336.73±2.08 ppm), apodeme (921.11±8.12 ppm), Gut (129.94±13.8 ppm) and apodeme (4.16±0.54 ppm) samples, respectively while lowest concentrations of metals were observed in gut (Fe = 556.61 ppm), mouth (Zn = 605.36 ppm), leg tissue (Cu = 60.85 ppm) and leg tissues (Cd = 2.12 ppm). Results clearly showed that bioaccumulation of essential metal concentration in all the analyzed body parts were higher than non-essential heavy metals with the flow of metals in Fe>Zn>Cu>Cd order. Statistical predictions revealed that bioaccumulation of metals were not significantly influenced by weight, total length and carapace width of the animal. The heavy metal accumulations in samples were higher than the national and international permissible limit range hence not suitable for human consumption.